Activation of Akt–mTORC1 signalling reverts cancer‐dependent muscle wasting. Issue 1 (6th November 2021) - Geremia, Alessia; Sartori, Roberta; Baraldo, Martina; Nogara, Leonardo; Balmaceda, Valeria; Dumitras, Georgia Ana; Ciciliot, Stefano; Scalabrin, Marco; Nolte, Hendrik; Blaauw, Bert
Abstract: Background: Cancer‐related muscle wasting occurs in most cancer patients. An important regulator of adult muscle mass and function is the Akt–mTORC1 pathway. While Akt–mTORC1 signalling is important for adult muscle homeostasis, it is also a major target of numerous cancer treatments. Which role Akt–mTORC1 signalling plays during cancer cachexia in muscle is currently not known. Here, we aimed to determine how activation or inactivation of the pathway affects skeletal muscle during cancer cachexia. Methods: We used inducible, muscle‐specific Raptor ko (mTORC1) mice to determine the effect of reduced mTOR signalling during cancer cachexia. On the contrary, in order to understand if skeletal muscles maintain their anabolic capacity and if activation of Akt–mTORC1 signalling can reverse cancer cachexia, we generated mice in which we can inducibly activate Akt specifically in skeletal muscles. Results: We found that mTORC1 signalling is impaired during cancer cachexia, using the Lewis lung carcinoma and C26 colon cancer model, and is accompanied by a reduction in protein synthesis rates of 57% ( P  < 0.01). Further reduction of mTOR signalling, as seen in Raptor ko animals, leads to a 1.5‐fold increase in autophagic flux ( P  > 0.001), but does not further increase muscle wasting. On the other hand, activation of Akt–mTORC1 signalling in already cachectic animals completely reverses the 15–20% loss in muscle mass and force ( P  < 0.001). Interestingly, Akt activation only in skeletal muscle completely normalizes the transcriptional deregulation observed in cachectic muscle, despite having no effect on tumour size or spleen mass. In addition to stimulating muscle growth, it is also sufficient to prevent the increase in protein degradation normally observed in muscles from tumour‐bearing animals. Conclusions: Here, we show that activation of Akt–mTORC1 signalling is sufficient to completely revert cancer‐dependent muscle wasting. Intriguingly, these results show that skeletal muscle maintains its anabolic capacities also during cancer cachexia, possibly giving a rationale behind some of the beneficial effects observed in exercise in cancer patients.